Spectrophotometric Determination of Sulfamethoxazole Following Simple Diazotization and Coupling with Diphenylamine - Khalaf, Husam S.; Al-Haidari, Abdul Mohsin A.; Dikran, Sarmad B.; Mohammed, Alaa K. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Simple, sensitive, accurate and inexpensive spectrophotometric methods have been developed for the determination of sulfamethoxazole (SMZ) in pure and dosage forms. This method is based on diazotization of primary amine group of sulfamethoxazole with sodium nitrite and hydrochloric acid followed by coupling with diphenylamine in acidic medium to obtain a stable blue colored dye and show a maximum absorption (max) at 530 nm. Different variables affecting the completion of reaction have been carefully optimized, following the classical univariate sequence and modified simplex method. Beer’s law is obeyed in the concentration range of (0.5-12.0 µg.mL-1) with molar absorptivity of 4.9617×104 L.mol-1.cm-1. The limit of detection was (0.108 µg.mL-1), and Sandell’s sensitivity value 5.1047 µg.cm-2. The proposed method was successfully applied to the determination of sulfamethoxazole in pharmaceutical preparation